Acute Upper Gastrointestinal Bleeding: A Hands-On Simulation Case for Internal Medicine Residents Improves Knowledge and Confidence - Marni H. Wilkoff; Emily S. Seltzer; Nicholas R. Piniella; Harrindra Seepersaud; Priscilla Loanzon; Susannah Kurtz; James Salonia; Daniela Jodorkovsky (MedEdPORTAL, 2025)
Introduction Upper gastrointestinal (GI) bleeding leads to approximately 350,000 hospital admissions annually. Simulation-based training enhances medical education by improving quality care, patient safety, and clinical competency. To increase internal medicine (IM) residents’ exposure to critical GI concepts, we developed a GI bleed simulation curriculum. Methods A total of 129 IM residents participated in a hands-on simulation using a high-fidelity manikin. Pre- and postsimulation surveys assessed demographics, confidence, and knowledge. The case involved a 45-year-old male with alcohol use disorder, hematemesis, and hemodynamic instability. Key learning outcomes included assessing vitals, performing a physical exam, initiating resuscitation, ordering appropriate medication, consulting GI, and creating a differential. Critical equipment included a code cart and moulage blood. A postsimulation debrief addressed the management of esophageal varices (EV), peptic ulcer disease (PUD), central venous access, massive transfusion protocol, and hemorrhagic shock. Results Confidence improved for PGY 1 and PGY 2 residents in all categories (p < .05). PGY 3 residents increased their confidence managing EV (p = .03), PUD (p = .002), and outpatient EV (p = .003). PGY 1 and PGY 2 knowledge increased with treatment of nonvariceal GI bleeds (p < .001, p = .001). All residents increased in their knowledge of timing of endoscopy for EV bleeds (p < .001). Among all residents combined, there was an increase in knowledge of discharge medications for EV and PUD (p = .01). Discussion A hands-on simulation curriculum positively impacted IM residents’ confidence and knowledge in managing GI bleeds, highlighting its educational value.